Acceptability for the influenza virus vector COVID-19 vaccine for intranasal spray: A cross-sectional survey in Beijing, China - Yuan Ma; Juan Li; Yanlin Cao; Wei Li; Rujing Shi; Bin Jia; Haihong Wang; Le Yan; Luodan Suo; Weizhong Yang; Jiang Wu; Luzhao Feng (Taylor & Francis Group, 2023)
The intranasal spray COVID-19 vaccine was made available for the first time in China, it is necessary to understand receivers' satisfaction and experience toward the vaccine to help optimize vaccination service. A self-administered multicenter cross-sectional questionnaire survey was conducted in Beijing, China, in December 2022. The vaccination experience was evaluated through three dimensions: immediate tolerance, smooth progress, and time-saving. Vaccine acceptability was measured by receivers' preference for the intranasal spray over intramuscular injection after vaccination and their recommendation willingness. Stepwise multinomial and binary logistic regression models were applied to investigate factors associated with vaccine acceptability. Among 10,452 participants included in the analysis, 92.6% felt no discomfort during the inoculation, 99.8% thought the vaccination process went well, and 89.4% deemed it a time-saving option. For vaccine acceptability, 5566 (53.3%) participants were willing to recommend the vaccine to others, 534 (5.1%) refused, and 4352 (41.6%) had not decided yet; 6142 (58.8%) participants preferred the intranasal spray, 873 (8.4%) preferred the intramuscular injection, and 3437 (32.9%) had no preferences. The most concerned aspects of the intranasal spray vaccine were vaccine effectiveness and safety. Receivers who perceived higher vaccine effectiveness or safety were more likely to recommend it to others (OR, 95%CI: 4.41, 3.24-6.00; 6.11, 4.52-8.27) or prefer it over intramuscular injection after vaccination (OR, 95%CI: 5.94, 4.62-7.65; 8.50, 6.70-10.78). Receivers showed good acceptability and experience toward the intranasal spray COVID-19 vaccine. Vaccine effectiveness and safety were the most concerned aspects, and corresponding publicity and education efforts may help improve vaccine acceptability.